2020
DOI: 10.1002/ptr.6909
|View full text |Cite
|
Sign up to set email alerts
|

A standardized extract of Danggui Buxue Tang decoction selectively exerts estrogenic activities distinctly from tamoxifen

Abstract: More and more menopausal women use Danggui Buxue Tang (DBT) for relieving their symptoms. Concerns for its safety have been raised as it contains phytoestrogen and acts via estrogen receptors (ERs). Our study aimed to determine whether DBT could selectively exert estrogenic activities and interact with tamoxifen in bone, brain, uterus, and breast by using ovariectomized (OVX) rats and ER-positive cells. In OVX rats, DBT induced a 31.4% increase in bone mineral density and restored the mRNA expression of dopami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Development of bone is focusing on the processes and mechanisms by which “cell number, position, shape, and patterns of connectivity are set during embryonic and early postnatal life.” The proteomic enrichment analyses suggest that the up regulated proteins, triggered by DBT, but not by DBT ∆cal , are actin filament, cell junction, banded collagen fibril components, ECM-receptor, tropomyosin and Rho GTPase: the regulations of these proteins are in accord to rapid cytoskeleton dynamics and bone regeneration ( Dallas and Bonewald, 2010 ; Huck et al, 2020 ). In addition, the identified pathways relating to bone differentiation are enriched in the enrichment analysis, in consistent with our previous reports in vitro and in vivo ( Choi et al, 2011 ; Gong et al, 2015 ; Zhou et al, 2018 ; Zhou et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…Development of bone is focusing on the processes and mechanisms by which “cell number, position, shape, and patterns of connectivity are set during embryonic and early postnatal life.” The proteomic enrichment analyses suggest that the up regulated proteins, triggered by DBT, but not by DBT ∆cal , are actin filament, cell junction, banded collagen fibril components, ECM-receptor, tropomyosin and Rho GTPase: the regulations of these proteins are in accord to rapid cytoskeleton dynamics and bone regeneration ( Dallas and Bonewald, 2010 ; Huck et al, 2020 ). In addition, the identified pathways relating to bone differentiation are enriched in the enrichment analysis, in consistent with our previous reports in vitro and in vivo ( Choi et al, 2011 ; Gong et al, 2015 ; Zhou et al, 2018 ; Zhou et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…The results suggested that the hormonal pathway was not the direction that DBT followed. Instead, the estrogen-like effects were the result of the two herbs combination [ 11 12 ]. Platform studies have also revealed the scientific basis of the ancient wisdom of mixing the two herbs together so as to achieve clinical synergy.…”
Section: Discussionmentioning
confidence: 99%
“…Calycosin alone, however, did not trigger on the estrogenic activities. Recently, Zhou et al [ 12 ] demonstrated that the estrogen-like properties of DBT was also distinctly different from drugs commonly used to mimick estrogen therapy like tamoxifen which is considered cancer-safe. Besides estrogenic property, systems biology analysis of DBT-treated cultures suggested the enhancement of energy metabolism [ 13 ], and improvement of mitochrondial bioenergetics [ 14 ].…”
Section: Introductionmentioning
confidence: 99%